Utilizing Text-to-Speech Technology: Natural Reader in Teaching Pronunciation - Fitria, Tira Nur (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
This research stimulates the use of Natural Reader Text-to-Speech (TTS) in teaching pronunciation. This research is descriptive qualitative. The analysis shows the steps of using Natural Readers. Teachers/lecturers can click https://www.naturalreaders.com/. They can log in or register into the account. If they have an account, they can continue or click “Continue with Google” or “Continue with Apple”. They can type a word, sentence, or text in the column box, or click the + icon to upload documents in Word or Pdf. They can set the type of native speaker sound (male or female), volume, and speed of pronunciation before playing/listening to the pronunciation. When all the settings have been done, they click the play icon to hear the native speaker say that have been inputted. Teachers/lecturers can ask students to follow the native speakers to say the words or sentences so the students can pronounce English words correctly and fluently. They may quickly produce or export audio into MP3 files. The Natural reader app provides a text-to-speech converter solution for both websites and mobile apps. Natural Reader converts text into sound English with various accents such as British or American even other accents. This application has a free version, but the paid version has more complete features to be used in teaching and learning English pronunciation. This tool is capable of synthesizing the human voice from the previously entered text input. Natural Readers provide substantial text-to-speech support to meet a variety of student needs in English pronunciation.